Therapeutic effect of indirubin-loaded bovine serum albumin nanoparticules on ulcerative colitis. (24th March 2022) - Yu, Guang-Min; Zhou, Li-Feng; Liu, Xiao-Ming; Liu, Bin; Lai, Xue-Ying; Xu, Chu-Lan; Long, Ming-Yi; Zhu, Yan-Ming; Wang, Ji-De; Li, Ming-Song
Abstract : The therapeutic effect of indirubin on dextran sulfate sodium-induced colitis in mice and 3D cultured biopsies from patients was further enhanced by the nano-carrier system, making it a highly promising medical candidate for ulcerative colitis. Abstract : Indirubin is considered to have promising potential in the treatment of ulcerative colitis (UC). However, poor aqueous solubility and low bioavailability limit its clinical application. We produced indirubin-loaded bovine serum albumin nanoparticles (INPs) and characterized their drug encapsulation efficiency, drug-loading capacity, capacity to release indirubin in vitro and short-term physical stability. We also investigated the pharmacokinetics of INPs in mice. We then compared the curative effects of INPs and indirubin against dextran sulfate sodium-induced colitis in mice and 3D cultured biopsies from patients with UC. In the mouse model, the outcomes of INP treatment, including the disease activity index and serous levels of interleukin (IL)-1β and IL-10, were significantly different from those of indirubin treatment. Similarly, when we administered INPs and indirubin to the ex vivo colonic tissues of patients with UC, the effect of INPs was stronger than that of indirubin for most antioxidant and anti-inflammatory biomarkers. The results of both the animal trial and ex vivo experiment indicate that the therapeutic effect of indirubin was further enhanced by the carrier system, making it a highly promising medical candidate for UC.